2018
DOI: 10.18240/ijo.2018.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transconjunctival sutureless 27-gauge vitrectomy for vitreoretinal diseases

Abstract: The current results suggest that 27G PPV system is a safe and effective treatment for various vitreoretinal diseases. When learning to perform 27G PPV, surgeons may encounter a learning curve and should gradually expand surgical indications from easy to pathologically complicated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…An adequate membrane peeling was achieved with both 25-gauge and 27-gauge forceps. It is important to note that, with its smaller diameter, the 27-gauge cutter can more easily be placed in the space between the retina and the PVR membrane, which is helpful in membrane dissection [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate membrane peeling was achieved with both 25-gauge and 27-gauge forceps. It is important to note that, with its smaller diameter, the 27-gauge cutter can more easily be placed in the space between the retina and the PVR membrane, which is helpful in membrane dissection [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Hagen-Poiseuille law, this should theoretically result in a decrease in the flow rate by approximately 60%. However, dual pneumatically operated vitrectomy probes with ultrahigh cut rates (7500 cpm) can maintain an efficient vitreous flow rate [21]. High cut rate lowers vitreous viscosity, resulting in reduced resistance to flow.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to lower flow/suction in 27G instrumentation and has been reported by other authors. 6 By controlling for variables in a multiregression analysis, we revealed no association with indication for surgery, age, sex or axial length. Despite the high incidence of breaks, none of the patients in our series developed an immediate or late postoperative rhegmatogenous retinal detachment.…”
Section: Discussionmentioning
confidence: 74%
“…4 Since the initial report of a 27G transconjunctival sutureless vitrectomy system by Oshima and colleagues, 5 this technique has being widely adopted. While various authors [6][7][8][9] have confirmed its safety and efficacy compared to traditional smallgauge vitrectomy systems, the risk for iatrogenic retinal breaks has not been quantified thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-Incision Vitrectomy Surgery (MIVS) offers an excellent safety profile for patients, while the newest 27-gauge (27G) systems have potential additional safety and outcome benefits when compared to earlier MIVS platforms. This innovation towards progressively smaller instrumentation is playing a major role in the evolution of posterior segment surgery by allowing for decreased incision size and, possibly, less pain, [ 1 , 2 ] fewer post-surgical wound leaks and subsequently, faster recovery times [ 3 5 ] with a low risk of other post-operative complications ( 6 8 ). Specifically, multiple large cohort studies and a 2013 literature review concluded there was no increased risk of endophthalmitis when comparing MIVS to 20-gauge (20G) vitrectomy [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%